INTERPRETASI JALAN DENGAN METODA KOMPUTASI GEOMETRI PROYEKTIF - Akmal
Abstract: A prototype of Road Interpretation software using Computational Projective Geometry approach has been developed. This software, called InterJal, is developed by using Object-Oriented Method from Coad and Yourdon. The prototype is implemented using Delphi 1.0 Compiler in the Microsoft Windows platform. The use of computational projective method facilities easy road boundary detection via the computation of vanishing points from intersection of parallel lines. Computational Projective Geometry is a representation of geometrical relationship involving points and lines by unit vector in terms of N-vector. Processing in this system involves image enhancement by equalization and filtering, edge detection, line detection by using Hough Transform, and lastly interpretation process by determining correspondence points of two road boundaries and transforming all points and lines to N-vector